Managing Teacher Competence in Islamic-Based Vocational Education: A Comparative Case Study - Harun Lubis; Agus Salim Salabi; Muhammad Anggung Manumanoso Prasetyo; Amir Karimi (AT-TA'LIM, 2025)
Teacher competence management is a critical factor in sustaining Islamic-based vocational education, particularly within diverse institutional contexts. This study explores and compares the management of teacher competence development at MAN 1 Samarinda and MAN 1 Langsa, two madrasahs with contrasting structural and contextual conditions. Employing a comparative qualitative approach, data were gathered through in-depth interviews, observations, and document analysis involving madrasah leaders, vocational teachers, and relevant stakeholders. The findings reveal distinctive management patterns. MAN 1 Samarinda applies a structured and systemic model supported by adequate infrastructure, strong industry and university partnerships, and government involvement, enabling continuous professional development and industry-aligned vocational learning. Conversely, MAN 1 Langsa faces limitations in facilities, training access, and industry collaboration; however, it sustains teacher competence development through strong Islamic value orientation, leadership commitment, social capital, and community engagement. Across both contexts, Islamic values function as a foundational framework that shapes leadership practices, curriculum implementation, and teacher professional growth. Key challenges include infrastructural constraints, limited certification opportunities, and uneven industry involvement. Nevertheless, enabling factors—such as visionary and transformational leadership, alumni networks, and university partnerships—mediate these constraints and support adaptive competence development. Based on these findings, this study proposes an integrative management framework that connects Islamic values, leadership, and contextual strategies in developing pedagogical, professional, social, and personality competencies of vocational teachers. This study contributes a value-based and context-sensitive perspective on Islamic vocational education management and provides practical implications for madrasah leaders and policymakers in aligning employability demands with ethical and spiritual foundations.